Courtship diverges with foraging behaviour in artificially selected populations. (October 2018) - Cole, Gemma L.; Endler, John A.
Abstract : The sensory drive hypothesis proposes that natural selection on certain behaviours will alter sensory system properties and result in correlated evolution of unrelated behaviours reliant on that sensory system. Here, we used artificially selected populations to demonstrate that selection on colour-based foraging behaviour is associated with divergence of male sexual display behaviour. In a previous experiment, populations of guppies, Poecilia reticulata, were selected for increased chase behaviour towards a red or a blue prey item. In this study, we conducted behavioural trials using these artificially selected populations to show that male mating behaviour diverged after artificial selection on foraging behaviour. The behavioural trials showed that the number of courtship displays and total mating activity were reduced in populations selected to chase a red prey item compared to control populations and populations selected to chase a blue prey item. These results show that artificial selection for a given behaviour can result in changes in unrelated behaviours. Our study has shown that selection on a nonmating behaviour may have consequences for sexual behaviour and the evolution of sexual signalling that has previously not been considered. Highlights: We previously selected for foraging behaviour towards red and blue stimuli. Populations selected to chase red responded strongly to artificial selection. We tested selected populations for differences in reproductive behaviour of males. We found differences in behaviour of the males between the selected populations. Populations selected to chase red showed less courtship behaviour than controls.